Logic-based program synthesis and transformation : 27th International Symposium, LOPSTR 2017, Namur, Belgium, October 10-12, 2017, Revised selected papers /: 27th International Symposium, LOPSTR 2017, Namur, Belgium, October 10-12, 2017, Revised selected papers. (2018) - Unknown
No abstract available